Implementation Of Corporate Social Responsibility Islamic Economic Perspective at PT. Bank Sumut Syariah Branch Padangsidimpuan - Nofinawati, Nofinawati; Efendi, Sulaiman; Hayati, Rini (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research is based on corporate social responsibility which is a program of activities of a company that must be carried out in accordance with the mandate of Law no. 40 of 2007 concerning PT. the purpose of this study is to determine the implementation of corporate social responsibility in the perspective of Islamic Economics at PT. Bank Sumut Padangsidimpuan Sharia Branch. The study used a descriptive qualitative approach with interview, observation, and documentation study data collection techniques to the employees of Bank Sumut Syariah Branch Padangsidimpuan which was then analyzed using data reduction, data presentation, and verification. The results showed that the implementation of corporate social responsibility at PT. Bank Sumut Padangsidimpuan Sharia Branch by implementing the Community Development Program (PBL), the first; aspects of the development of public infrastructure facilities such as the construction of shelters and monuments, the second; educational aspects such as providing scholarships and purchasing research tools for related universities. Islamic Economics Review on the implementation of corporate social responsibility at PT. Bank Sumut Padangsidimpuan Sharia Branch has complied with the basic principles of Islamic Economics, namely maslahah (public interest)Keywords: Social Responsibility, Islamic Economy